STRUCTURE AND LANGUAGE IN WRITING THE TEXT OF FILM / DRAMA STUDENTS CLASS XI - Deden Kurnia; Euis Eti Rohaeti; Enung Nurhayati (IKIP Siliwangi, 2021)
In the current curriculum, Curriculum 2013, the text becomes the main concept which develops the learning material. As for one of the material taught in the 2013 curriculum is the text of a film / drama review. The film / drama’s review texts discussed in the 2013 curriculum require the students be able to produce the review texts which suitable with their language structure and rules. Therefore in this study the author observes the analysis of structure and rules, especially among the sentences in writing of a film / drama review text by a class XI student. It uses a qualitative research approach with descriptive methods.The data source in this study is based on document. It is a collection of text reviews of films / plays by students of class XI. The objects of research are class XI or second grade of senior high school. This research using documentation and questionnaires as a data collection technique. The data is collected by using a test technique. The test is carried out with the same film for all students, a film from a TV drama entitled